2014
DOI: 10.1186/s40623-014-0156-0
|View full text |Cite
|
Sign up to set email alerts
|

X-ray absorption near edge structure spectroscopic study of Hayabusa category 3 carbonaceous particles

Abstract: Analyses with a scanning transmission x-ray microscope (STXM) using x-ray absorption near edge structure (XANES) spectroscopy were applied for the molecular characterization of two kinds of carbonaceous particles of unknown origin, termed category 3, which were collected from the Hayabusa spacecraft sample catcher. Carbon-XANES spectra of the category 3 particles displayed typical spectral patterns of heterogeneous organic macromolecules; peaks corresponding to aromatic/olefinic carbon, heterocyclic nitrogen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 32 publications
4
55
0
Order By: Relevance
“…The Itokawa particles returned by the first Hayabusa mission, for example, were shown to be composed of proteic amino acids at blank levels only (Naraoka et al 2012). Their results were supported by several other preliminary analyses of the Itokawa particles (e.g., Raman spectroscopy, X-ray absorption near edge structure (XANES) spectroscopy) (Kitajima et al 2015;Uesugi et al 2014;Yabuta et al 2014), which suggested that although organic materials were present, it was difficult to ascertain their extraterrestrial origin. Other than identifying amino acids that have rare biological occurrence and determining the relative amino acid abundances and enantiomeric ratio, stable isotope ratio is a reliable and convenient tool used to tell apart terrestrial and extraterrestrial amino acids, as biology preferentially uses lighter isotopes, while amino acids formed by abiotic processes in cold environments are more enriched in heavier isotopes.…”
Section: Introductionsupporting
confidence: 59%
“…The Itokawa particles returned by the first Hayabusa mission, for example, were shown to be composed of proteic amino acids at blank levels only (Naraoka et al 2012). Their results were supported by several other preliminary analyses of the Itokawa particles (e.g., Raman spectroscopy, X-ray absorption near edge structure (XANES) spectroscopy) (Kitajima et al 2015;Uesugi et al 2014;Yabuta et al 2014), which suggested that although organic materials were present, it was difficult to ascertain their extraterrestrial origin. Other than identifying amino acids that have rare biological occurrence and determining the relative amino acid abundances and enantiomeric ratio, stable isotope ratio is a reliable and convenient tool used to tell apart terrestrial and extraterrestrial amino acids, as biology preferentially uses lighter isotopes, while amino acids formed by abiotic processes in cold environments are more enriched in heavier isotopes.…”
Section: Introductionsupporting
confidence: 59%
“…The aliphatic C-H stretching of RA-QD02-0120, taking into account the presence of calcium carbonate Yabuta et al 2014), suggests various origins of the category 3 particles, although this particle belongs to the same subtype (blocky) as RB-QD04-0047-02. However, polyimide/polyamide resin is a major candidate for the source material of the particles.…”
Section: Comparison Between Category 3 Particles and Artificial Substmentioning
confidence: 99%
“…In this investigation, as a part of the sequential analysis of category 3 particles, we examined three category 3 particles (RB-QD04-0001, RB-QD04-0047-02, and RA-QD02-0120) by micro-Raman and Fourier transform infrared (FTIR) spectroscopies, together with several artificial carbonaceous substances including the 'white object' found in the sample container. The artificial substances are analyzed in order to get a clue as to whether the category 3 particles are extraterrestrial or not, and our data should be coupled with the results of other kinds of analyses (NanoSIMS, time-of-flight secondary ion mass spectrometry (ToF-SIMS), and X-ray absorption near edge structure (XANES) described in a series of articles in this issue Ito et al 2014;Yabuta et al 2014;Naraoka et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The Hayabusa sample catcher contained contaminants in the form of carbon-rich particles and inorganic particles Ito et al, 2014;Yabuta et al, 2014;Yada et al, 2014). Contamination to the Hayabusa2 samples must be minimal and any possible contamination should be recognized in advance.…”
Section: Requirements For Sampling and The Hayabusa2 Samplermentioning
confidence: 99%